Rancang Bangun Sistem Informasi Inventory Yang Dilengkapi Oleh Peramalan Stock Inventory Menggunakan Metode Autoregresif Integrated Moving Average (ARIMA) (Studi Kasus : UD.SANUSI) - Utami, Maulinda Devi; Purwanto, Eko; Nurmalitasari, Nurmalitasari (Politeknik Indonusa Surakarta, 2021)
Trading business is an activity of buying and selling goods or services with the aim of making a profit, without changing the condition of the product being sold. There are many types of trading businesses in Central Java, one of which is a building material equipment trading business trading business which is engaged in building material equipment itself carries out buying and selling activities for building goods such as stones, meters, screwdrivers, etc. UD.SANUSI is a trading business engaged in building tools owned by individuals. UD.SANUSI continues to grow today, it affects the number, types of items, and existing purchases. Due to the large number of requests, UD.SANUSI tries to meet market demand by completing the types of goods and stock available at the store. With advances in existing technology, it can be facilitated with an information system that will help the process of predicting goods using the ARIMA (Autoregressive Integrated Moving Average) calculation model. from the sales data obtained from the calculation results, ACF and PACF can be analyzed that ACF (p,q) is cut after lag 2 (q - p) and PACF is cut after lag 2 (p - q) with the results of P-Value AR (1 ) 0.000, P-Value MA (1) 0.000, P-Value Constant 0.019 and MSE of 20.9631.